IMPORTANCE OF SWITCHED MODE POWER SUPPLY - BAIDYA, PROSANTA; MONDA, MD.NOOR MAHAMMADL; BERA, SWARNENDU; SARKAR, SAIKAT (International Journal of Multidisciplinary Research and Studies, 2019)
Switched Mode Power supplies are important for use in personal computers and several other electronic instruments. The main cause of the using switched mode power supply is to provide quality power supply to the equipment’s which prevents unwanted damage of those. The proposed scheme is designed and simulated by using PSIM electronic simulation software. The obtained results show better performance of the power supply with respect to its output voltage regulation and input power quality.